2021
DOI: 10.1021/acs.jpcc.0c10165
|View full text |Cite
|
Sign up to set email alerts
|

Disordered but Efficient: Understanding the Role of Structure and Composition of the Co–Pt Alloy on the Electrocatalytic Methanol Oxidation Reaction

Abstract: A systematic investigation of the electrocatalytic Methanol Oxidation Reaction (MOR) was carried out using a model Co:Pt alloy system with different compositions and structural arrangements of the Co and Pt atoms. The structural variations with the same alloy composition included those with disordered arrangement of Co and Pt atoms in a face-centered cubic (fcc) lattice and ordered arrangements in face-centered tetragonal (fct) lattices. Our investigations clearly show that structures with disordered arrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Previously, we have reported a DFT study for PtCo binary alloy catalysts with different compositions and tested them as catalysts for MOR . In this study, it was concluded that an increase in electron density on Pt significantly improves the electrochemical performance of Pt-based catalysts. ,, The current results also endorse this postulation.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Previously, we have reported a DFT study for PtCo binary alloy catalysts with different compositions and tested them as catalysts for MOR . In this study, it was concluded that an increase in electron density on Pt significantly improves the electrochemical performance of Pt-based catalysts. ,, The current results also endorse this postulation.…”
Section: Resultssupporting
confidence: 72%
“…The incorporation of extra transition metals like Mn and Co into Pt in a Pt 100– x (MnCo) x /C (16 < x < 41) catalyst is expected to modify the electronic structure of the Pt surface, promote reaction kinetics, facilitate electron transfer, and also accelerate the removal of CO molecules to improve MOR catalytic activity, as has been confirmed in numerous reports. , These findings, as summarized in Figure , help to explain why the trimetallic Pt 100– x (MnCo) x /C (16 < x < 41) catalyst is active as compared to Pt/C. Previously, we have reported a DFT study for PtCo binary alloy catalysts with different compositions and tested them as catalysts for MOR . In this study, it was concluded that an increase in electron density on Pt significantly improves the electrochemical performance of Pt-based catalysts. ,, The current results also endorse this postulation.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The increasing global energy and environmental crisis promote the development of clean and renewable energy technology. As a green portable power source, direct methanol fuel cells (DMFCs) are the proper alternatives to traditional fossil fuels because of their higher energy density, stable conversion efficiency and low pollutant emission 1,2 . Currently, Pt‐based materials are widely used as an anode catalyst in DMFCs, but the low abundance, high cost and easily poisoning of Pt catalyst by CO‐like intermediates (COads), and poor durability of operation have been decreased the catalytic reaction efficiency significantly limited its commercialization worldwide 3 .…”
Section: Introductionmentioning
confidence: 99%
“…As a green portable power source, direct methanol fuel cells (DMFCs) are the proper alternatives to traditional fossil fuels because of their higher energy density, stable conversion efficiency and low pollutant emission. 1,2 Currently, Pt-based materials are widely used as an anode catalyst in DMFCs, but the low abundance, high cost and easily poisoning of Pt catalyst by CO-like intermediates (COads), and poor durability of operation have been decreased the catalytic reaction efficiency significantly limited its commercialization worldwide. 3 And these disadvantages have triggered the research for promising catalyst support that can enable the Pt to distribute uniformly with low consumption and greatly enhance the electrocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%